Experimental analysis of velocity fields in hot extrusion of aluminium alloy 6351 - Martins M. (2012)
Hot extrusion is a metal forming process with a huge importance in the manufacturing of long metallic bars with complex shapes, and because of this, academics and industries are especially interested in better understanding how metal flows during the process. In order to have a reliable computational tool that can help to solve and to obtain material internal flow, experimental tests and numerical simulation with the finite element method were carried out to obtain results of the velocity fields generated in hot direct extrusion of aluminum billets (aluminum alloy 6351). The experimental results of the velocity field will be used to validate a computational code based on the finite volume method. © (2012) Trans Tech Publications.